Cotula Cinerea دراسة الالتحام الجزيئي والتنبؤ بخصائص لمركبات الزيت الاساسي - شريط يسرى; جابوربي انتصار (جامعة الوادي - university of eloued, 2024)
This study aims to determine the biological effectiveness of 20 compounds of the essential oil of the Cotula Cinerea plant towards TyrRS for S. aureus tyrosyl-tRNA synthetase, Cyclooxygénase, Desulfo-Xanthine Oxidas, Acetylcholinesterase, Abl kinase, which are responsible for inhibiting bacterial, inflammatory, oxidative, Alzheimer’s, and cancer activity. By studying molecular docking via computer. In this work, the Autodock program was used to evaluate the interactions between target compounds and proteins and their pharmacological and toxicological properties using SwissADME and ProToxII, which allowed the prediction of various properties such as: solubility, potential toxicity, intestinal and cerebral absorption, etc. The results obtained showed that there are 5 compounds: with high binding energy towards the active site of the studied proteins: Germacrene B, α-Bisabolol, Neryl isobutyrate, and Bisabolol Oxide A, where the free binding energy reached (-9.01 kcal/mol, -7.97 kcal/mol, 8.05). - kcal/mol, -8.49 kcal/mol and -8.80 kcal/mol, respectively). According to the results obtained, these compounds were more active compared to other compounds toward the aforementioned proteins, which makes them candidates to be biologically effective toward bacterial, inflammatory, oxidative, Alzheimer’s, and cancer activity.
فيزيولوجيا النبات والتنوع الحيوي
Keywords: Cotula Cinerea; molecular docking; ADMET; Autodock.